Drug-Induced Sarcoid-like Reactions Associated to Targeted Therapies and Biologic Agents - Federica Andolfi; Luca Caffarri; Matilde Neviani; Silvia Rubini; Dario Andrisani; Filippo Gozzi; Bianca Beghé; Enrico Clini; Roberto Tonelli; Stefania Cerri (Diagnostics)
Background: Sarcoidosis is a multisystem inflammatory disease characterized by the immune-mediated formation of non-necrotizing epithelioid granulomas. Several commonly used medications can induce similar granulomatous reactions, known as drug-induced sarcoid-like reactions (DISRs), which closely mimic sarcoidosis. Despite their specificity in targeting molecular pathways, certain therapies—particularly targeted treatments—have increasingly been linked to DISRs. Methods: This narrative review was based on a PubMed search using the terms “SARCOID LIKE REACTION” and “DRUG”. A cross-check was performed with “SARCOID” combined with each identified drug to identify misclassified cases. Drugs with limited evidence or weak pathogenetic plausibility were excluded, leaving only molecularly targeted therapies for consideration. Sources included case reports, case series, and reviews selected based on their clinical and scientific relevance, without any restrictions on time or language. Results: In light of the available data, five main pharmacological groups were found to be associated to DISR: immune checkpoint inhibitors, TNF-α antagonists, BRAF inhibitors, monoclonal antibodies, and miscellaneous agents. Each group has distinct mechanisms of action and clinical indications, which likely affect the frequency, presentation, and timing of DISRs. Conclusions: Diagnosing DISRs is challenging, and a structured approach is crucial for differentiating them from other conditions. To support clinicians, we propose a diagnostic algorithm to guide decision-making in suspected cases. Management should be individualized, as most DISRs either resolve spontaneously or improve after the discontinuation of the causative drug. Important factors influencing therapeutic decisions include the severity of the underlying disease, the availability of alternative treatments, and the extent of DISR manifestations.